High-energy Gamma-Ray and Neutrino Emissions from Interacting Supernovae Based on Radiation Hydrodynamic Simulations: A Case of SN 2023ixf - Shigeo S. Kimura; Takashi J. Moriya (The Astrophysical Journal)
Recent observations of core-collapse supernovae revealed that the existence of dense circumstellar matter (CSM) around their progenitors is ubiquitous. Interaction of supernova ejecta with such a dense CSM is a potential production site of high-energy cosmic rays (CRs), gamma rays, and neutrinos. We estimate the gamma-ray and neutrino signals from SN 2023ixf, a core-collapse supernova occurred in a nearby galaxy M101, which exhibits signatures of the interaction with the confined, dense CSM. Using a radiation-hydrodynamic simulation model calibrated by the optical and ultraviolet observations of SN 2023ixf, we find that the CRs cannot be accelerated in the early phase because the sharp velocity jump at the shock disappears due to strong radiation pressure. Roughly 4 days after the explosion, the collisionless subshock is formed in the CSM, which enables the CR production and leads to gamma-ray and neutrino emissions. The shock sweeps up the entire dense CSM roughly 9 days after the explosion, which ceases the high-energy radiation. Based on this scenario, we calculate the gamma-ray and neutrino signals, which have a peak around 9 days after the explosion. We can constrain the CR production efficiency to be less than 10% by comparing our prediction to the Fermi Large Area Telescope upper limits. Future multimessenger observations with an enlarged sample of nearby supernovae will provide a better constraint on the CR production efficiency in the early phases of supernovae.